Actividad fotocatalítica de películas de TiO2 sensibilizadas con complejos metálicos (2017)
It was done an analysis of TiO2 films sensitized with nickel and cobalt (II) metal complexes contained in ligands derived from 3.5-dimethylpyrazole. A preliminary study was carried out on the effect of the substrate cleaning protocol and the calcination temperature of unmodified TiO2 films. A modification of the films was carried out using the dip coating method, varying the solvent used in the dilution of the complexes and the time of the heat treatment after the modification. Finally, the photocatalytic activity of the modified films was evaluated by means of the degradation of methylene blue in the presence of ultraviolet radiation and visible light.